Early Childhood Education in The Digital Era: A Systematic Review of Cognitive Development, Inclusive Pedagogy, Family Influence, and Child Well-Being - Eko Risdianto; Mona Ardina; Mohammad Qais Rezvani; Hamed Barjesteh (Journal of Early Childhood Development and Education, 2026)
Background: Early Childhood Education (ECE) has undergone significant transformation in the digital era due to rapid technological advancement, evolving family dynamics, and increasing attention to inclusive education and child well-being. Despite these developments, existing studies remain fragmented and often fail to integrate cognitive development, digital learning, family influence, inclusive pedagogy, and child well-being within a unified framework. Objective: This study aims to systematically analyze research trends, identify existing research gaps, and explore future directions in ECE in the digital era, with a focus on cognitive development, inclusive pedagogy, family influence, and child well-being. Method: A Systematic Literature Review (SLR) combined with bibliometric analysis was employed using publications indexed in the Scopus database. Relevant articles were identified through a structured keyword search and screened based on predefined inclusion and exclusion criteria. Data cleaning was conducted using OpenRefine, while VOSviewer and Biblioshiny were utilized to perform network visualization, thematic mapping, and trend analysis. Results: The findings reveal a notable shift in ECE research from clinically oriented and fragmented approaches toward more integrative and multidisciplinary perspectives. The literature predominantly emphasizes child development, parental involvement, and early intervention. Recent studies increasingly focus on the role of digital technologies in learning environments, particularly in the post-pandemic period. However, technology integration remains insufficiently connected to pedagogical principles. Furthermore, gaps persist in incorporating inclusive education, cultural diversity, and child well-being into digital learning contexts. Conclusion: Advancing ECE in the digital era requires a holistic and integrated approach that combines cognitive and social development, technology-enhanced pedagogy, family and cultural engagement, and child well-being. Such integration is essential for developing adaptive, inclusive, and sustainable early childhood education systems while contributing to educational psychology and child development research.